Evaluating the Factors Affecting Users’ Satisfaction of the ABSHR E-Services System in the Kingdom of Saudi Arabia - Al-Enezi, Fahad Nawaf Ayed (Journal of Economic, Administrative and Legal Sciences, 2022)
The main objective of this study is to evaluate the factors that affect users’ satisfaction of the ABSHR system in Saudi Arabia. An in-depth study was conducted by using qualitative and quantitative approaches. Two questionnaires were used in this study. The first questionnaire was used to evaluate the users’ satisfaction with ABSHR system with a sample of 676 respondents, who are the actual ABSHR system actual users. It was designed to elicit information about the relationship of the four dimensions that determine the attitudes toward ABSHR use, and it was found that benefits, cost, risk, and opportunity have a significant positive relationship with the users’ satisfaction. Generally, the results also showed that the degree of acceptance of the ABSHR system is at a good level. Benefits, cost, opportunity, and customer satisfaction are at a good level according to users’ responses. Whereas, risk factor is at an acceptance level. The demographic characteristics variance was conducted and it was found that there are no statistically significant differences except gender with risk and opportunity. The second questionnaire evaluated the ABSHR system of employees’ attitudes toward electronic systems by obtaining their opinions. Therefore, data were obtained from 51 respondents. The results showed that the relative advantage, complexity, compatibility, trialability, and observability have a significant positive relationship with the attitude toward electronic systems. The result also showed that the degree of acceptance, in general, of the ABSHR system is at a very good level with relative advantage, complexity, observability, and attitude toward electronic systems according to employees’ responses. Whereas, compatibility and triability factors are at an excellent level of acceptance. Employees’ demographic information was tested and found that education and experience have no statistically significant differences, while age and job title have statistically significant differences. The study recommended to keep the ABSHR e-services system always updated to improve the users’ satisfaction in addition, to providing new e-services and improving the existing ones.
Keywords: e-government; Sadad; Information technology; Relative advantage; Benefits; Compatibility; Opportunity